A bioorthogonal turn-on fluorescent strategy for the detection of lysine acetyltransferase activity. Issue 44 (16th May 2018) - He, Maomao; Han, Zhen; Qiao, Jing; Ngo, Liza; Xiong, May P.; Zheng, Y. George
Abstract : Bioorthogonal labelling was applied to design "turn-on" fluorescent probes for sensitive and selective detection of histone acetyltransferase enzymatic activity in a simple mix-and-read manner. Abstract : Lysine acetylation plays vital roles in the regulation of fundamental cellular processes, which is mediated by lysine acetyltransferases (KATs). Developing chemical biology probes for KAT activity detection is of important value in providing improved understanding of their biological functions. We reported a panel of "turn-on" fluorescent probes for sensitive and selective detection of KAT enzymatic activity through a simple mix-and-read format. Combined with bioorthogonal substrate labelling and click chemistry, these probes produced strong "turn-on" fluorescent signals in response to KAT-mediated acylation process. This chemical biology strategy diversifies the assay toolboxes to investigate functions and mechanisms of acetyltransferase enzymes.